Å gå med i pasienten si livsverd. Tankar omkring ei sjukepleieforteljing - Lid, Else Marie; Kvigne, Kari; Roghell, Per Kristian (Nordisk tidsskrift for helseforskning, 2016)
Based on a nursing experience from a Norwegian local hospital, we reflect on the personal narrative in the story presented as well as on essential caring near the end of life. Important questions are: What will the challenging tasks be in nursing following a patient´s life world? How does such a practice and way of being in the world affect the relationship between nurse and patient? The focus of discussion is how a nurse possibly can be open, receiving and personal connected, and through such a practice be able to support patients to live their lives in spite of life threatening illness. The authors emphasize the existential dimensions of the relationship between a nurse and a patient. The nurse can support her patients to express themselves in many different ways, in her communication. For this to happen depends on the nurse´s ability to be open and personally present in her meeting with the patient.